On the Public Economics of Annuities with Differential Mortality - Antoine Bommier; Marie-Louise Leroux; Jean-Marie Lozachmeur (ETH Zurich, CER-ETH - Center of Economic Research, 2010)
This paper studies the problem of redistribution between individuals having different mortality rates. We use a continuous time model in which there are two types of individuals characterized by different survival probability paths. Individual preferences are represented by a generalized life-cycle utility function which can exhibit temporal risk aversion. We successively compare utilitarian allocations when individuals exhibit temporal risk neutrality and temporal risk aversion. This problem is analyzed in the contexts of full information and asymmetric information on mortality rates.
Keywords: H55; H23; I31; 330; Uncertain Lifetime; Redistribution; Annuities; Nonlinear Taxation; Finanzmathematik; Steuerbelastung; Einkommensverteilung; Sterblichkeit; Lebenszyklus; Vollkommene Information; Asymmetrische Information; Theorie